A Suite of System Dynamics T&L Simulations and Games Based Upon the Australian Qualifications Framework (AQF). Issue 4 (1st October 2020) - McGrath, G. Michael; Blaer, Madelene; Williams, Melanie; Wilson-Evered, Elisabeth; Whitelaw, Paul
ABSTRACT: The paper details the specification of a model that will underpin the development of system dynamics based teaching and learning simulations across five of the nine levels of the Australian Qualifications Framework (AQF). The model functions as a scaffold, building on previous levels of knowledge and simulation experience to guide students as they progress to higher levels of learning. It is anticipated this will enable students who reach AQF Level 9 to have developed a strong understanding of system dynamics and interactivity between model variables, as well as complex cause-and-effect decision-making and unintended consequences, culminating in their ability to define and specify their own variables so as to enhance models.